The Comintern - Hallas, Duncan (Haymarket Books, 2008)
This history of the Communist (Third) International, from its beginnings in 1919 as the center of world revolution through its degeneration at the hands of the Stalinist bureaucracy, draws out lessons valid today to the work of building bridges to unite and rebuild a Left capable of fighting for radical social change.